Developing new measures of charisma and vision. - Tan, Gary Ting Wei. (2008)
Existing measures of charisma and vision are based on Western leadership, therefore they face validity and reliability issue when applied to the Singapore context. The objective was to develop new measures of charisma and vision that are appropriate to Singaporean leadership, and to test their relationship and effectiveness.